Post-accession transposition of EU law in the new member states: a cross-country comparison - Knill, Christoph; Tosun, Jale (European integration online papers, 2009)
In this paper we examine the transposition of European Union (EU) legislation in the twelve ‘new’ member states during the post-accession stage. To this end, we scrutinize the number of formal notice letters received by the new member states in the period from 2004 to 2007. Our analysis shows that there is considerable variation in the transposition behaviour. While Lithuania, Hungary as well as Slovenia are the best performers, the transposition of EU legislation is less effective in Bulgaria, the Czech Republic, and particularly Romania. The comparatively high number of transposition shortcomings by this latter country group clearly indicates that even the process of incorporating European provisions into domestic law is far from unproblematic, which suggests the existence of even more substantive problems with the practical side of implementation. The results of our descriptive analysis show that transposition failure is predominantly related to the degree of trade with the EU, bureaucratic capacity and pre-accession policy alignment. We conclude that in the intermediate-term increasing bureaucratic capacities and stronger economic ties with the EU may help to reduce transposition failures.